2020
DOI: 10.3390/genes11070804
|View full text |Cite
|
Sign up to set email alerts
|

Glia and Neural Stem and Progenitor Cells of the Healthy and Ischemic Brain: The Workplace for the Wnt Signaling Pathway

Abstract: Wnt signaling plays an important role in the self-renewal, fate-commitment and survival of the neural stem/progenitor cells (NS/PCs) of the adult central nervous system (CNS). Ischemic stroke impairs the proper functioning of the CNS and, therefore, active Wnt signaling may prevent, ameliorate, or even reverse the negative effects of ischemic brain injury. In this review, we provide the current knowledge of Wnt signaling in the adult CNS, its status in diverse cell types, and the Wnt pathway’s impact on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 193 publications
(223 reference statements)
0
18
0
Order By: Relevance
“…Functional enrichment analysis of the genes that were differentially expressed in samples from mice treated with cisplatin + MRS5980 vs cisplatin alone identified “positive regulation of Wnt signaling pathways” and pathways related to protein synthesis. Wnt signaling has been shown to play an important role in repair especially in the survival of neural stem cells/progenitor cells and regulation of BDNF release, a neurogenic niche which is mandatory for intact cognitive capabilities [ 25 , 41 ]. We and others showed that cisplatin treatment depletes the neurogenic niche [ 9 , 42 ], therefore upregulation of Wnt signaling in response to MRS5980 could be an instrumental signaling pathway to restore cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Functional enrichment analysis of the genes that were differentially expressed in samples from mice treated with cisplatin + MRS5980 vs cisplatin alone identified “positive regulation of Wnt signaling pathways” and pathways related to protein synthesis. Wnt signaling has been shown to play an important role in repair especially in the survival of neural stem cells/progenitor cells and regulation of BDNF release, a neurogenic niche which is mandatory for intact cognitive capabilities [ 25 , 41 ]. We and others showed that cisplatin treatment depletes the neurogenic niche [ 9 , 42 ], therefore upregulation of Wnt signaling in response to MRS5980 could be an instrumental signaling pathway to restore cognition.…”
Section: Discussionmentioning
confidence: 99%
“…The work in our current postnatal studies would suggest that NSCs that endow the postnatal DG develop in an altered trajectory after IUGR. In the mammalian brain, activated NSCs in the DG give rise to proliferating neural progenitor cells, differentiate to DCX + neuroblasts, which gradually mature to terminally differentiated neurons ( Knotek et al, 2020 ). During mid-development of postnatal DG, DCX + neuroblasts have smaller cell volumes with higher mean dendritic lengths in our IUGR offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects of active Wnt signaling were also observed in our previous study on neonatal NS/PCs ( Kriska et al, 2016 ). Additionally, it has been shown that hypoxia and FCI increase the number of NS/PCs in the hippocampus and SVZ, promote the expansion of neuroblasts 1 month after MCAO, and that canonical Wnt signaling is involved in this process ( Cui et al, 2011 ; Zhang et al, 2014 ; Knotek et al, 2020 ). The importance of Wnt signaling in the differentiation of NS/PCs to neurons under ischemic conditions was also documented by Zhang et al (2016) .…”
Section: Introductionmentioning
confidence: 99%